One-Day Many-Problems:A Problem Based Learning Approach - Hegade, Prakash (Journal of Engineering Education Transformations, 2019)
Problem Based Learning not only improves problem-solving abilities but also promotes the development of critical thinking skills, involvement in the team, communication skills, comprehending the reflections, and all of the mentioned along with understanding and applying the course content. A considerable number of universities have experimented with variants of problembased learning on a variety of course content delivery. The methodology has its challenges of crafting a good ill-structured problem, delivery techniques, evaluation parameters, scaffolding, etc. The problem-based learning sessions usually require lengthier time due to inherent nature, while most universities have class hour sessions of one to two hours. Also, the problem-based sessions are generally effective in smaller classrooms of strength up to thirty. This paper presents the One-Day Many-Problems approach, a teaching-learning model, which helps to craft questions, facilitate discussions, trigger motivation, provide reflections, and comprehend using scaffolding activities. The sessions are planned to engage the classes in intervals where a chain of sessions sum up to inclusive conclusions - the approach aids in the attainment of expected course learning outcomes with systematic and meticulous planning and execution. The paper further presents a case study of the model applied to an eight-semester course – Model Thinking. The paper discusses the results and ponders over the achievement of course learning outcomes along with general guidelines and learnings. One-Day Many-Problems approach proves to be a beneficial delivery model for a shorter session and larger strength classrooms.